Problems Encountered in Distance Teaching Practices Course and Solution Suggestions - Alanoglu, Muslim; Karabatak, Songul; Karabatak, Murat (Ieee, 2021)
This study aimed to examine the problems experienced by senior students studying at education faculties in the distance Teaching practice (DTP) course, where they participated in practice activities in formal schools due to the Covid-19 pandemic, and the suggestions for solving them. To achieve this aim, the students' opinions, who were determined with purposive sampling in the study conducted with a qualitative research design, were collected with open-ended questionnaires. The results obtained from the study are as follows: (1) The DTP process provided teacher candidates with experience in distance education, increased their technology predispositions, prevented the total interruption of education due to the pandemic, prevented the further spread of the pandemic, and ensured that trainings were conducted independently of time and place. (2) In the DTP process, communication problems between the parties (school administrators, counselors, and students), technical problems, technical impossibilities, inexperience, indifference, and inadequacy of technology use emerged as fundamental problems. (3) For the DTP process to be more effective, teaching practice courses should be fully face-to-face, or the DTP process should not only be conducted by distance education but should also be supported by face-to-face education processes.
9th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 28-29, 2021 -- Firat Univ, Elazig, TURKEY
Keywords: Teaching Practice; Distance Teaching Practice; education faculties